Generalized Grand Lebesgue Spaces Associated to Banach Function spaces - Alireza Bagheri Salec; Seyyed Mohammad Tabatabaie; Alaa Mahdi Talib Albeka (Sahand Communications in Mathematical Analysis)
In this paper we introduce the class of grand Lebesgue spaces associated to a Banach function space $X$ by replacing the role of the $L^1$-norm by the norm $\|·\|_X$ in the classical construction of the generalized grand Lebesgue spaces. Also, we study the inclusion property of these spaces.